Improving lysine production through construction of an Escherichia coli enzyme‐constrained model. Issue 11 (21st July 2020) - Ye, Chao; Luo, Qiuling; Guo, Liang; Gao, Cong; Xu, Nan; Zhang, Li; Liu, Liming; Chen, Xiulai
Abstract: Microbial cell factories are widely used for the production of high‐value chemicals. However, maximizing production titers is made difficult by the complicated regulatory mechanisms of these cell platforms. Here, k cat values were incorporated to construct an Escherichia coli enzyme‐constrained model. The resulting ec_ i ML1515 model showed that the protein demand and protein synthesis rate were the key factors affecting lysine production. By optimizing the expression of the 20 top‐demanded proteins, lysine titers reached 95.7 ± 0.7 g/L, with a 0.45 g/g glucose yield. Moreover, adjusting NH4 + and dissolved oxygen levels to regulate the synthesis rate of energy metabolism‐related proteins caused lysine titers and glucose yields to increase to 193.6 ± 1.8 g/L and 0.74 g/g, respectively. The ec_ i ML1515 model provides insight into how enzymes required for the biosynthesis of certain products are distributed between and within metabolic pathways. This information can be used to accurately predict and rationally design lysine production. Abstract : Due to the complicated regulatory mechanisms, it is difficult to maximize the production titers of microbial cell factories. Here, an Escherichia coli enzyme‐constrained model, named ec_iML1515, was constructed by incorporating kcat values. Using ec_iML1515 model, the protein demand and protein synthesis rate were identified as the key factors affecting lysine production. By combing the gene expression, and the optimization of NH4+ and dissolved oxygen, lysine titers and glucose yields to increase to 193.6 ± 1.8 g/L and 0.74 g/g, respectively.